Ultrasonic hearing and echolocation in the earliest toothed whales - Park, Travis (Biol Lett, 2016)
The evolution of biosonar (production of high-frequency sound and reception of its echo) was a key innovation of toothed whales and dolphins (Odontoceti) that facilitated phylogenetic diversification and rise to ecological predominance. Yet exactly when high-frequency hearing first evolved in odontocete history remains a fundamental question in cetacean biology. Here, we show that archaic odontocetes had a cochlea specialized for sensing high-frequency sound, as exemplified by an Oligocene xenorophid, one of the earliest diverging stem groups. This specialization is not as extreme as that seen in the crown clade. Paired with anatomical correlates for high-frequency signal production in Xenorophidae, this is strong evidence that the most archaic toothed whales possessed a functional biosonar system, and that this signature adaptation of odontocetes was acquired at or soon after their origin.